Radiation Stability of Triple Coatings Based on Transition-Metal Nitrides Under Irradiation By Alpha Particles and Argon Ions; Russian Physics Journal; Vol. 59, iss 1 - Potekaev A. I. Aleksandr Ivanovich; Kislitsyn S. B. Sergey Borisovich; Uglov V. V. Vladimir Vasilievich; Klopotov A. A. Anatoly Anatoljevich; Gorlachev I. D. Igor Dmitrievich; Klopotov V. D. Vladimir Dmitrievich; Grinkevich L. S. Larisa Sergeevna (2016, 2016)
Title screen